Zero Trust Implementation Challenges in Legacy and Wireless Network Systems - Poonam Chakravarty; Jigar Pandya; Rishita Sangani; Disha Panchal (International Journal of Wireless Security and Networks, 2025)
This article titled "Zero Trust Implementation Challenges in Legacy Systems and Wireless Network Systems" delves into the evolving landscape of cybersecurity, emphasizing the inadequacy of traditional perimeter-based security models in the face of modern cyber threats. The Zero Trust Security framework is highlighted as an essential advancement in this scenario, emphasizing the core idea of "never trust, always verify." This paradigm shift underscores the importance of continuous verification, least privilege access, and micro-segmentation of wired and wireless networks to mitigate risks associated with insider threats and compromised credentials. However, the implementation of Zero Trust principles is particularly challenging in sectors such as healthcare, government and manufacturing, where legacy systems and wireless network systems often lack essential security features like multi-factor authentication and real-time monitoring. These outdated infrastructures pose significant barriers to adopting a robust Zero Trust environment, necessitating a careful balance between enhancing securities and maintaining operational efficiency. The article further explores the multifaceted challenges organizations face when integrating Zero Trust principles within legacy and wireless network environments. Key hurdles include compatibility issues with existing technologies, operational disruptions during migration, limitations in data visibility and monitoring, compliance constraints, and cultural resistance to change. Every challenge is deeply tied to the distinct features of legacy systems, which were built without consideration for today's security standards. To address these issues, the study proposes practical strategies such as micro-segmentation and software-defined perimeters, highlighting case studies that illustrate successful implementations across various sectors. Ultimately, the document aims to enrich the cybersecurity modernization dialogue by providing insights and solutions for organizations striving to enhance their security posture while navigating the complexities inherent in transitioning from legacy systems to a Zero Trust architecture.
Keywords: Zero Trust Security; cybersecurity challenges; legacy systems; micro-segmentation; wireless network security